2021
DOI: 10.1016/j.nicl.2021.102587
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of brainstem monoaminergic fibre tracts in multiple sclerosis as a putative mechanism for cognitive fatigue: a fixel-based analysis

Abstract: Highlights We compared monoaminergic fibre tracts integrity in multiple sclerosis and controls. Integrity was studied by diffusion-MRI and tractography, using fixel-based analysis. Axonal damage within selective monoaminergic tracts was found in multiple sclerosis. Dopaminergic and noradrenergic axonal damage was associated with cognitive fatigue. Our results support the hypothesis that monoamines contribute to multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 71 publications
2
31
0
Order By: Relevance
“…Numerous other neuroimaging studies also support this notion (see (Almutairi et al, 2020;Cook et al, 2017;Gay et al, 2016;Josev et al, 2019;Manca et al, 2021;Shan et al, 2020;Shan et al, 2018;Tanaka et al, 2006;Van Der Schaaf et al, 2018, 2017Wortinger et al, 2017;Wortinger et al, 2016)). Furthermore, Carandini et al (2021) found an inverse correlation between levels of mental fatigue and DA tract abnormalities in MS. Carandini et al (2021) suggested that this is evidence of dopaminergic abnormalities underlying mental fatigue, as hypothesised by Dobryakova et al (2015). Research in animals, and in patients given cytokine therapies, has demonstrated that peripheral inflammation can lead to central dopaminergic hypofunction (Anisman et al, 1996;Felger et al, 2013;Felger and Miller, 2012;Lee et al, 2021).…”
Section: Dopaminementioning
confidence: 89%
“…Numerous other neuroimaging studies also support this notion (see (Almutairi et al, 2020;Cook et al, 2017;Gay et al, 2016;Josev et al, 2019;Manca et al, 2021;Shan et al, 2020;Shan et al, 2018;Tanaka et al, 2006;Van Der Schaaf et al, 2018, 2017Wortinger et al, 2017;Wortinger et al, 2016)). Furthermore, Carandini et al (2021) found an inverse correlation between levels of mental fatigue and DA tract abnormalities in MS. Carandini et al (2021) suggested that this is evidence of dopaminergic abnormalities underlying mental fatigue, as hypothesised by Dobryakova et al (2015). Research in animals, and in patients given cytokine therapies, has demonstrated that peripheral inflammation can lead to central dopaminergic hypofunction (Anisman et al, 1996;Felger et al, 2013;Felger and Miller, 2012;Lee et al, 2021).…”
Section: Dopaminementioning
confidence: 89%
“…In addition, dopamine has been shown to modulate the gut–brain axis, which plays an important role in the development of autoimmunity, psychiatric disorders, and neuroinflammation [ 15 , 16 , 17 ]. It is important to note that depression is one of the most common symptoms in MS and may aggravate its course, which could be explained by similar pathogenetic mechanisms of MS and depression, including an enhanced Th17 immune response [ 18 , 19 ]. Conversely, the clinical efficacy of “controlled stress” therapies, such as treatment with antidepressants, lifestyle modification, and coping strategies in MS, was shown [ 10 , 20 , 21 ].…”
Section: The Involvement Of Dopamine In the Development Of Clinical Symptoms In Msmentioning
confidence: 99%
“…On the other hand, secondary dysregulation of catecholamines in MS due to neuroinflammation and structural damage of catecholamine-dependent pathways within the brain was shown [ 18 , 24 , 25 ]. In particular, Carandini et al showed that axonal damage imbalances dopamine and norepinephrine neurotransmission in relapsing–remitting MS patients [ 18 ]. They also showed a central role of the dopamine mesocorticolimbic pathway in fatigue in MS [ 18 ].…”
Section: The Involvement Of Dopamine In the Development Of Clinical Symptoms In Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, FBA accounts for both macrostructural (fiber bundle) and microstructural (within voxel) changes within WM, providing a more comprehensive understanding of intra-axonal and fiber tract changes. Accordingly, FBA has been used in several neurological disorders including Parkinson's disease (37,38), multiple sclerosis (39,40), traumatic brain injury (41,42), schizophrenia (42), and healthy aging (43). FBA can be used to estimate fiber density (FD) within a fiber bundle, the fiber bundle cross section (FC), or a combined measure, fiber density cross section (FDC).…”
Section: Introductionmentioning
confidence: 99%